Dramatic versus Post-dramatic Textuality: Paradoxes of a (False?) Opposition - Čale Feldman, Lada (2009)
The paper is a polemic response to current attempts to minimize the difference between the dramatic and the postdramatic use of textual material, especially to recent arguments espoused by W. B. Worthen regarding drama's inherent performativity. Arguing instead that postdramatic theatre treats the text in a post-structuralist sense, as a "body" of its own, the paper offers three authorial concepts in the recent Croatian theatre history in which text is treated as an autonomous material clashing with and almost obstructing rather than supporting representation.